2001
DOI: 10.1159/000050606
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the β-Catenin Gene in Gastric Carcinomas

Abstract: Previous studies reported that mutation of the adenomatous polyposis coli (APC) gene was not observed in the majority of gastric cancers. To evaluate the role of the APC/β-catenin/Tcf pathway, we analyzed mutations in the β-catenin gene and the accumulation of β-catenin protein in gastric carcinomas. An interstitial deletion spanning exon 3 of the β-catenin gene was observed in 1 of 13 gastric cancer cell lines. No missense mutation was found in these 13 cell lines. Nuclear and/or cytoplasmic localization of β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
5
34
1
1
Order By: Relevance
“…By contrast, to our knowledge, mutations in APC or CTNNB1 have been SFRPs methylation in gastric cancer M Nojima et al reported for only four cell lines (Table 1) (Caca et al, 1999;Yokozaki, 2000;Sasaki et al, 2001;Ku and Park, 2005). Of those, two (MKN74 and AZ521) were found to harbor the same mutation at codon 1450 of APC, a CGA-TGA transition, which leads to truncation of the protein (Sasaki et al, 2001). A GGA-GAA transition at codon 34 (G34E) in CTNNB1 was found in AGS cells (Caca et al, 1999), and an ACC-GCC change at codon 41 (T41A) in CTNNB1 was detected in SNU638 cells (Ku and Park, 2005).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…By contrast, to our knowledge, mutations in APC or CTNNB1 have been SFRPs methylation in gastric cancer M Nojima et al reported for only four cell lines (Table 1) (Caca et al, 1999;Yokozaki, 2000;Sasaki et al, 2001;Ku and Park, 2005). Of those, two (MKN74 and AZ521) were found to harbor the same mutation at codon 1450 of APC, a CGA-TGA transition, which leads to truncation of the protein (Sasaki et al, 2001). A GGA-GAA transition at codon 34 (G34E) in CTNNB1 was found in AGS cells (Caca et al, 1999), and an ACC-GCC change at codon 41 (T41A) in CTNNB1 was detected in SNU638 cells (Ku and Park, 2005).…”
Section: Resultsmentioning
confidence: 80%
“…Our results confirmed activation of the Wnt signaling pathway in half of the GC cell lines tested, although the apparent degree of activation varied. By contrast, to our knowledge, mutations in APC or CTNNB1 have been SFRPs methylation in gastric cancer M Nojima et al reported for only four cell lines (Table 1) (Caca et al, 1999;Yokozaki, 2000;Sasaki et al, 2001;Ku and Park, 2005). Of those, two (MKN74 and AZ521) were found to harbor the same mutation at codon 1450 of APC, a CGA-TGA transition, which leads to truncation of the protein (Sasaki et al, 2001).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations